Students’ Perceptions toward Speaking Achievement and Critical Thinking on the Use of British Parliamentary Debating System - Yunda Lestari (ELS Journal on Interdisciplinary Studies in Humanities, 2018)
The aims of this study are to find out (1) what are the students’ perceptions toward speaking achievement on the use of British Parliamentary Debating System; (2) what are the students’ perceptions toward critical thinking on the use of British Parliamentary Debating System. The study conducted as an experimental method. Non-equivalent control group design was applied in this study. The population of this study was all semester students of English Study Program of Baturaja University in the academic year 2017/2018 with the total number of population is 118. Cluster random sampling was used in taking the sample. The total numbers of students as samples are 51 students. Students who belong to the experimental group had been taught by using British Parliamentary Debate. The questionnaire was used as the instrument in identifying the students’ perceptions of BP Debate toward speaking achievement and critical thinking. The questionnaire was distributed after the posttest in the experimental group. The result showed that most of the students thought that British Parliamentary Debating System stimulated critical thinking actively, easier students in giving argument constructively, helped students in giving the relevant argument and to find the way in making or providing good arguments. BP Debate also stimulated creative thinking and most of them thought that British Parliamentary Debating System stimulated critical thinking actively, easier students in giving argument constructively, helped students in giving the relevant argument and to find the way in making or providing good arguments. BP Debate also stimulated creative thinking.